LNG-IUS vs. medical treatments for women with heavy menstrual bleeding: A systematic review and meta-analysis - Chen, Sijing; Liu, Jianhong; Peng, Shiyi; Zheng, Ying (Frontiers in Medicine, 2022)
Introduction To compare efficacy and safety of the levonorgestrel-releasing intrauterine system (LNG-IUS) with medical treatments for women with heavy menstrual bleeding. Material and methods We searched PubMed, Embase, the Cochrane Central Register of Controlled Trials, China National Knowledge Infrastructure (CNKI), and Wanfang databases for relevant randomized controlled trials (RCTs) in November 2021. All meta-analyses were performed using random-effects model. PROSPERO registration number: CRD42021295379. Results Thirteen trials (with 14 references) reporting on 1677 women were included in this systematic review. The majority of the included RCTs was rated with low-to-unclear risk of bias in selection, detection, attrition, reporting and other bias. All RCTs were rated as high risk in performance bias because blinding was difficult to ensure on the compared groups. Results of meta-analyses revealed that the number of clinical responders was greater in LNG-IUS group than that in medical treatments group at both 6-month (steroidal: 5 RCTs; n = 490; RR: 1.72 [1.13, 2.62]; I2 = 92%; nonsteroidal: 1 RCT; n = 42; RR: 2.34 [1.31, 4.19]) and 12-month (steroidal: 3 RCTs; n=261; RR: 1.31 [1.01, 1.71]; I2 = 74%) endpoints, with no clear differences on number of dropouts, and the incidence of adverse events. Conclusions Evidence indicates that LNG-IUS is superior to the medical treatments on short- and medium-term clinical responses, blood loss control, compliance and satisfaction. Meanwhile, frequency of adverse events related to LNG-IUS is acceptable.